Pathways to Our Sustainable Future : A Global Perspective from Pittsburgh - DeMarco, Patricia M. (Book collections on Project MUSE., 2017)
ittsburgh has a rich history of social consciousness in calls for justice and equity. Today, the movement for more sustainable practices is rising in Pittsburgh. Against a backdrop of Marcellus shale gas development, initiatives emerge for a sustainable and resilient response to the climate change and pollution challenges of the twenty-first century. People, institutions, communities and corporations in Pittsburgh are leading the way to a more sustainable future. Examining the experience of a single city, with all of its social and political complexities and long industrial history, allows a deeper understanding of the challenges and opportunities inherent in adapting to a changing world. Choices for more sustainable pathways for the future include transforming the energy system, restoring infertile ground, and preventing pollution through green chemistry production. Throughout the book, case studies responding to ethical challenges give specific examples of successful ways forward. Inspired by Rachel Carson's voice of precaution in protecting the Earth, this is a book about empowerment and hope.